Arousal and Executive Alterations in Attention Deficit Hyperactivity Disorder (ADHD) - Martella, Diana; Aldunate, Nerea; Fuentes, Luis J.; Sánchez-Pérez, Noelia (Frontiers in Psychology, 2020)
Attention deficit hyperactivity disorder (ADHD) is the most common neurobehavioral disorder in childhood and can significantly affect a child’s personal and social development and academic achievement. Taking into account the model of attentional networks proposed by Posner et al., the aim of the present study was to review the literature regarding two main explicative models of ADHD, i.e., the inhibition model and the cognitive-energetic model, by discussing behavioral and neurological evidence of both models and the limitations of each model. The review highlights evidence that favors the energetic model and points to an unstable arousal as a potential pathogenetic factor in ADHD.